2021
DOI: 10.1021/acs.nanolett.1c00364
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Assisted Rashba Splitting and Circular Photogalvanic Effect in Aqueously Synthesized 2D Dion–Jacobson Perovskite Crystals

Abstract: Recently, a two-dimensional Dion–Jacobson (DJ) perovskite (AMP)­PbI4 (AMP = 4-(aminomethyl)­piperidinium) is emerging with remarkable Rashba effect and ferroelectricity. However, the origin of the giant Rashba splitting remains elusive and the current synthetic strategy via slow cooling is time- and power-consuming, hindering its future applications. Here, we report on an economical aqueous method to obtain (AMP)­PbI4 crystals and clarify the origin of the giant Rashba effect by temperature- and polarization-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…As shown in Figure 2c, d, the data can be fitted by a power-law function I PL ∼ I ex k . 7,23,24 The intensity-dependence slope k values of PEA before and after formation of the heterojunction are ∼1.5 and ∼1.3, respectively, within the range of the freeand bound-exciton emission. 23 Considering that PEA is ptype, 25,26 the slight decrease in k suggests the reduced hole doping effect of PEA after interfacing with MBA.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…As shown in Figure 2c, d, the data can be fitted by a power-law function I PL ∼ I ex k . 7,23,24 The intensity-dependence slope k values of PEA before and after formation of the heterojunction are ∼1.5 and ∼1.3, respectively, within the range of the freeand bound-exciton emission. 23 Considering that PEA is ptype, 25,26 the slight decrease in k suggests the reduced hole doping effect of PEA after interfacing with MBA.…”
mentioning
confidence: 81%
“…3,17,18 According to theoretical calculations (the insets of Figure 1c and Supporting Note IV), the CPL activity of R-and S-MBA originates from spin-polarized carriers in the conduction and valence bands with giant spin splitting. 7,11 In stark contrast, there is no visible difference between σ − and σ + cases in PEA nanosheets with all three methods (Figure 1b). These results reveal that PEA perovskite does not exhibit any inherent CPL activity, either in the detection/emission or in the case like TMDs.…”
mentioning
confidence: 90%
“…It is noteworthy that the g Iph was much higher than the g CD . This may be attributed to the spin-dependent carrier transition and collection upon circularly polarized illumination. …”
mentioning
confidence: 99%
“…This higher value than the thermal energy at room temperature (26 meV) confirms its high tolerability toward thermal quenching effects. Moreover, excitation power-dependent URTP spectra (Figure c) are measured, and it is found that URTP enhances gradually when the laser power of excitation is increased and the integrated URTP intensity vs excitation power can be well fitted by a power-law function; the intensity-dependence slope of about 0.89 (Figure S14) suggests that the significant nonradiative recombination is established due to the increasing triplet–triplet interaction at a higher excitation intensity. , …”
Section: Resultsmentioning
confidence: 97%
“…Moreover, excitation power-dependent URTP spectra (Figure 3c) are measured, and it is found that URTP enhances gradually when the laser power of excitation is increased and the integrated URTP intensity vs excitation power can be well fitted by a power-law function; 40 the intensity-dependence slope of about 0.89 (Figure S14) suggests that the significant nonradiative recombination is established due to the increasing triplet−triplet interaction at a higher excitation intensity. 41,42 It should be noted that RTP properties are also related to molecular aggregation. Thus, a series of mixed-cation 2D perovskites are prepared using 4MPEA and PEA as organic cations in different ratios to tune the packing structures of 4MPEA.…”
Section: ■ Results and Discussionmentioning
confidence: 99%